Values and the Rule of Law: Foundations of the European Union – An Inside Perspective from the ECJ - von Danwitz, Thomas (Potchefstroom Electronic Law Journal, 2018)
Let us remember what has been written, ratified and set into force with the Treaty of Lisbon. The preamble of the Charter of Fundamental Rights starts out by stating: "The peoples of Europe, in creating an ever closer union among them, are resolved to share a peaceful future based on common values." And it goes on: "Conscious of its spiritual and moral heritage, the Union is founded on the indivisible, universal values of human dignity, freedom, equality and solidarity; it is based on the principles of democracy and the rule of law. It places the individual at the heart of its activities, by establishing the citizenship of the Union and by creating an area of freedom, security and justice." Even if a cynic might have considered these words to be merely a lip service unlikely to disturb the power-play European governments were so eagerly engaged in, the Charter nonetheless became the supreme law of the land and the preferred tools of the trade of a rather awkward species of beings, already of bad repute for relying on the mere wording of legal acts, and even worse, for taking rights seriously: judges - in particular those of the European Court of Justice.